2020
DOI: 10.48295/et.2020.80.6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of unconventional roundabouts in the design of suburban intersections

Abstract: The paper focuses on the use of non-conventional roundabouts, such as turbo-roundabouts and flower-roundabouts, for the reduction of both functional and safety critical issues. The aim is to evaluate the effectiveness of non-conventional design schemes compared to conventional solutions through the implementation of vehicular traffic microsimulation techniques and swept path analysis. The work proposes two case studies in suburban areas characterized by the presence of road intersections affected by high traff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…Calibration methods, as discussed by various studies, should ensure accurate predictions [75,76]. A concise overview of select peer-reviewed studies from 2019 to 2023, primarily using PTV Vissim [77] and Aimsun [78], is provided in Table 4 [76,[79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98]. However, research on roundabouts has significantly expanded, reflecting the increasing interest in integrating smart features for enhanced functionality [11].…”
Section: Models Methods and Implications For Roundabout Operational A...mentioning
confidence: 99%
“…Calibration methods, as discussed by various studies, should ensure accurate predictions [75,76]. A concise overview of select peer-reviewed studies from 2019 to 2023, primarily using PTV Vissim [77] and Aimsun [78], is provided in Table 4 [76,[79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98]. However, research on roundabouts has significantly expanded, reflecting the increasing interest in integrating smart features for enhanced functionality [11].…”
Section: Models Methods and Implications For Roundabout Operational A...mentioning
confidence: 99%
“…The authors concluded that changes to the cross-over intersection angle increase safety levels by providing better channelization of traffic movements on the minor intersections of the DCFI and reducing the intersection footprint to be used at high-density urban locations (Khliefat et al, 2021). Using vehicle traffic microsimulation tools and sweeping route analysis, Ciampa et al (2020) compared the efficacy of unconventional design schemes to conventional solutions. The study analyzes the performance of the current state of the intersection with two design options, conventional and unconventional, in terms of average speed, queue length, time lost, vehicle maneuvering size, and so on.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This issue arises due to the rapid increase in vehicle ownership relative to population and income growth (Guzman et al, 2020). Unconventional intersections and interchanges (UAIDs) show their capability to reduce traffic congestion, improve traffic operation and increase infrastructure capacity (Alozi and Hussein, 2022;Alzoubaidi et al, 2021;Ciampa et al, 2020;Corriere and Guerrieri, 2013;ElKashef et al, 2021;Hadidi et al, 2022;Jewel et al, 2022;Mane and Pulugurtha, 2020). Fundamentally, UAIDs aim to increase the efficiency of major intersections by reducing the number of turning movements and signal phases.…”
Section: Introductionmentioning
confidence: 99%
“…Roundabouts are of particular interest because they are considered safer due to their ability to slow through traffic and reduce the number of conflict points. In fact, several studies indicate that roundabouts, both conventional and unconventional, are effective in reducing collisions resulting in injuries or fatalities [1][2][3][4]. The widespread use of roundabouts is also justified by their positive perception by road users [5,6].…”
Section: Introductionmentioning
confidence: 99%